PELESTARIAN WARISAN BUDAYA KOTA LAMA PALOPO - AS, Chalid; Nur, Muhammad; Tahir Muda, Khadijah; Yusriana (Universitas Hasanuddin, 2023)
Palopo is one of three municipalities in South Sulawesi. The historical value of the city of Palopo radiates through the distribution of old buildings that we can still see today. Concentrated in the city space, which is currently known as the